The Role of Sharia Capital Markets and Sharia Banking Financing In Indonesia's Economic Growth - Tatha Amelia Fretika; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
The role of the Sharia Capital Market as an investment alternative that is in accordance with Islamic sharia is linked to the economy in Indonesia nationally. This writing was processed using literature study methods obtained from various books, journals and other related references. It is felt that the increase in the number of sharia shares every year has not been able to drive the rate of economic growth in Indonesia optimally. Synergy between related parties is needed so that interest in investment in the Sharia capital market increases and can have a big impact on national economic growth. The financial sector plays an important role in encouraging a country's economic growth, of which the Sharia capital market and Sharia financing are part of it. This research aims to analyze the influence of the Sharia capital market represented by the variables of the Indonesian Sharia Stock Index (ISSI), Sharia Mutual Funds, and Corporate Sukuk as well as Sharia Banking Financing on economic growth in Indonesia.